Commodity cycles, inequality, and poverty in Latin America - Balakrishnan, Ravi,Lizarazo, Sandra,Santoro, Marika,Toscani, Frederik,Vargas, Mauricio (International Monetary Fund, 2021)
Over the past decades, inequality has risen not just in advanced economies but also in many emerging market and developing economies, becoming one of the key global policy challenges. And throughout the 20th century, Latin America was associated with some of the world's highest levels of inequality. Yet something interesting happened in the first decade and a half of the 21st century. Latin America was the only region in the World to have experienced significant declines in inequality in that period. Poverty also fell in Latin America, although this was replicated in other regions, and Latin America started from a relatively low base. Starting around 2014, however, and even before the COVID-19 pandemic hit, poverty and inequality gains had already slowed in Latin America and, in some cases, gone into reverse. And the COVID-19 shock, which is still playing out, is likely to dramatically worsen short-term poverty and inequality dynamics. Against this background, this departmental paper investigates the link between commodity prices, and poverty and inequality developments in Latin America
10.5089/9781484326091.087
Keywords: Graue Literatur; Armut; Einkommensverteilung; Vermögensverteilung; Rohstoffwirtschaft; Rohstoffpreis; Konjunktur; Bolivien; Brasilien; Peru; Paraguay; Lateinamerika; Economywide Country Studies; Equity; Justice; Inequality; and Other Normative Criteria; Welfare; Well-Being; and Poverty; Caribbean; Computable and Other Applied General Equilibrium Models; Poverty and Homelessness; Investments: Commodities; Welfare; Well-Being; and Poverty: General; Equity; Justice; Inequality; and Other Normative Criteria and Measurement; International Economics; Economywide Country Studies: Latin America; Economics: General; Commodity Markets; Aggregate Factor Income Distribution; Political economy; International institutions; Macroeconomics; Poverty & precarity; Investment & securities; Income inequality; National accounts; Commodities; Poverty; Equilibrium; Economics; Income distribution; Income; Commercial products; Prices